Peluang Pemanfaatan Big Data di Perpustakaan : Sebuah Kajian Literatur - Araf Aliwijaya; Hanny Chairany Suyono (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
Artificial Intelligence (AI) technology has the opportunity to be applied in libraries to improve services and meet user needs. AI can be used to speed up the process of finding information by users and making recommendations for collections of relevant library materials. This research will discuss how AI can be used in libraries, including the implementation of virtual reality, chatbots, voice recognition systems, robotics, and analysis systems. We will also cover documentation of implementing AI in other areas that have opportunities for implementation in libraries. The type of this research is qualitative using descriptive methods. Data sources were obtained from books, journals, activity reports, and websites that match the topic of the problem. This study found several examples of AI implementation in libraries, both those that have been done and those that have never been done and will be the future of libraries. The concept offered discusses how AI can work with librarians in providing better and more efficient services for users.